Eruption and caries status of first permanent molars in children aged 6-7 years: Status erupsi dan karies gigi molar pertama permanen pada anak usia 6-7 tahun - Adam Malik Hamudeng; Khadijah Meirani A; Afniati Rachmuddin; Andi Sri Permatasari (Makassar Dental Journal PDGI Makassar, 2026)
The prevalence of caries in children is very high, especially in the first permanent molars. The eruption status is an important milestone in a child's development, but it is also a phase that is vulnerable to the development of caries. This literature review explores the factors that influence the eruption status and caries of the first permanent molars in children aged 6-7 years. The first permanent molars are at high risk of caries due to pro-longed exposure to the oral environment. Factors such as genetics, nutrition, general health, and oral hygiene behaviour play a significant role in the eruption status and caries of the first permanent molars in children aged 6-7 years. It is concluded that a comprehensive preventive approach, including education, nutrition, and dental hygiene habits, is necessary to reduce the prevalence of caries in permanent first molars.